PENERAPAN ANALISIS SWOT DALAM MERANCANG STRATEGI PEMANFAATAN KOLEKSI DI PERPUSTAKAAN DESA BANTARSARI - Hendra wicaksono; Rochemin; Resya Fakhrunnisa (Administrasi Pendidikan Umbara Bogor, 2024)
The existence of a Village Library for Village Communities is an Informal Education facility for sources of knowledge and information. One of the village libraries located in Bantarsari Village is the Bantarsari Village Library. The availability of the Bantarsari Village library is already in the Bantarsari Village Office, Bogor. However, the existence of the Bantarsari Village Library is still minimal for the people of Bantarsari Village to visit. The purpose of this study was to formulate a design strategy for utilizing library collections based on SWOT analysis at the Bantarsari Village library. This research method is qualitative with a descriptive approach. The data collection technique used was structured interviews. The sampling technique used is purposive sampling. The informants in this study were two Bantarsari Village library staff who were used as key informants, and three Bantarsari Village Library users who were used as supporting informants. The data analysis technique used is the Miles and Huberman analysis model and uses SWOT analysis. The data validity technique used is triangulation of sources with member checks. The results of this study indicate that there is a search for a strategy for utilizing library collections based on SWOT analysis. The results of the search for strategies for utilizing library collections based on SWOT analysis are that there are factors from the external environment of the library which include opportunities (opportunities) and threats (threats) faced by the library, while factors originating from the internal environment identify the strengths (strengths) and weaknesses (weaknesses) that became the basis for developing strategies for utilizing library collections based on SWOT analysis in the Bantarsari Village library